(untitled) (International Journal of Engineering and Computer Science, 2024)
The arrival of digital payment technologies has brought unprecedented convenience to businesses and consumers. However, the rapid adoption of digital payments relies on both parties trusting the technology to handle their transactions securely and accurately. Conventional approaches to security issues rely on complex and frequent updates to the software that underpins digital payment systems, as well as cryptographic solutions that are challenging to implement and may, from time to time, require replacement as older systems are hacked. The introduction of biometric data-driven payment security enhances the current security systems, reducing system overheads, and increasing customer confidence in the technology. Our approach is to leverage advances in Artificial Intelligence (AI) systems, driven by the latest developments in big data technology. This novel combination is capable of improving the dynamic three-tier digital payment security model, ultimately reducing both fraud and overheads and increasing trust from both businesses and consumers.